LPmerge: an R package for merging genetic maps by linear programming - Endelman, Jeffrey B.; Plomion, Christophe (Bioinformatics, 2014)
Consensus genetic maps constructed from multiple populations are an important resource for both basic and applied research, including genome-wide association analysis, genome sequence assembly and studies of evolution. The LPmerge software uses linear programming to efficiently minimize the mean absolute error between the consensus map and the linkage maps from each population. This minimization is performed subject to linear inequality constraints that ensure the ordering of the markers in the linkage maps is preserved. When marker order is inconsistent between linkage maps, a minimum set of ordinal constraints is deleted to resolve the conflicts. Availability and implementation: LPmerge is on CRAN at http://cran.r-project.org/web/packages/LPmerge. Contact:  endelman@wisc.edu Supplementary information:  Supplementary data are available at Bioinformatics online.